COMPARISON OF EFFECTS OF MISOPROSTOL AND OMEPRAZOLE ON THE GASTROINTESTINAL COMPLICATIONS OF NONSTEROIDAL ANTI-INFLAMMATORY DRUGS - Tülay SARIÇAM; Nur ERSÖZ; Eser VARDARELİ; Ayşegül HARMANCI; Varol ŞAHİNTÜRK; Akif ALADAĞ; Esat ERENOĞLU (Turkish Journal of Gastroenterology, 2020)
-